PENGEMBANGAN MODUL PRAKTIKUM INTERAKTIF PADA PEMROGRAMAN BERBASIS WEB - Mukhamad Angga Gumilang; Syaad Patmanthara; Didik Dwi Prasetya (SENTIA 2016, 2016)
To do a practicum in web-based programming course, the student minimally needs three software, that is text-editor, ebook-reader, and browser. So that existing learning media can be developed further in interactive practicum module by providing training and evaluation features in one file. This study aims: (1) to Design, (2) to Develop and (3) to Test the validity of interactive practicum module on web-based programming courses. The study model is being used is a research model of 4D by Thiagarajan. The subject of this study were students year 2013 of undergraduate of informatic engineering that already finished web-based programming course. The technique of collecting data using questionnaires. To test the validity, evaluation conducted by a team of experts, limited-scale test, and wide scale test. The result of the study are follows: The review score from the expert learning materials is 88.64%, the review score from the expert instructional media is 94.27%. the score from limited-scale test is 80.88%, And the review score from wide scale test is 87.14%. From the results, it is concluded that the development product is eligible to being use in web-based programming course. The product has advantages included: Module has interactive features such as live-editor that can show the results of staticweb programming scripts.